A SOCIAL-SCIENTIFIC STUDY OF HONORING PARENTS IN THE WORLD OF THE APOSTLE PAUL AND ITS THEOLOGICAL IMPLICATIONS IN 1 CORINTHIANS 4:14–21 - CHEN, YONGLI (Université Saint-Paul / Saint Paul University, 2023)
This study postulates that an anthropological investigation of honor and grace (as opposed to honor and shame) will shed new light on Paul’s understanding of familial and spiritual parent-child relations in 1 Corinthians 4:14–21. It contends that Julian A. Pitt-Rivers’s grace—signifying reciprocity of hearts and the spirit of gift—is a more suitable paradigm to explore familial reciprocity and spiritual bonds between Paul and the Corinthians and between Christians and God in the social world of St. Paul, compared to previous social-scientific studies of family, honor, and reciprocity. Doing so demonstrates the inseparability of Paul’s language of family and grace in speaking of how the divine χάρις in the person of Jesus Christ (the Christ-gift and the life-giving spirit) creates the family of God and preserves all Christians to be more generous and grateful followers in the divine gift-economy. Moreover, we learn that Paul is a “gifted” apostle of Christ and is graced to be the first one to initiate the Christ-gift to the Corinthians and to act honorably by demonstrating his fatherly gratitude (χάρις) verbally and practically because of God’s superabundant χάρις in Christ. Finally, Paul’s appeal to his Corinthian children to become imitators of him is an invitation to participate willingly in Christ’s abounding grace in honor of him as a spiritual parent and for the glory of God.
Keywords: grace (χάρις), gratitude (χάρις), honor, the parent-child relations, non-reciprocity, the Christ-gift, and the spirit of gift (the life-giving spirit)